2018
DOI: 10.1111/jog.13791
|View full text |Cite
|
Sign up to set email alerts
|

Association of glutathione S‐transferase theta 1 and glutathione S‐transferase mu 1 gene polymorphism with the risk of pre‐eclampsia during pregnancy in Bangladesh

Abstract: GSTM1 null genotype increases the risk of pre-eclampsia. Combined GSTT1 and GSTM1 null genotype, the risk was even higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Two studies were excluded due to repeated data, 35,36 eventually leaving 10 articles with sufficient data about genotype frequencies of both GST M1 and GST T1 deletion polymorphism in women with preeclampsia and healthy pregnant controls, which were included in the final review. [20][21][22][23][24][37][38][39][40][41] A detailed description of the characteristics extracted from the included studies is shown in Table 1. Out of 2831 participants included in this systematic review, 1259 were preeclampsia cases and 1572 were controls.…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies were excluded due to repeated data, 35,36 eventually leaving 10 articles with sufficient data about genotype frequencies of both GST M1 and GST T1 deletion polymorphism in women with preeclampsia and healthy pregnant controls, which were included in the final review. [20][21][22][23][24][37][38][39][40][41] A detailed description of the characteristics extracted from the included studies is shown in Table 1. Out of 2831 participants included in this systematic review, 1259 were preeclampsia cases and 1572 were controls.…”
Section: Data Extractionmentioning
confidence: 99%
“…Five out of ten researches investigated frequencies of combined GST M1 and GST T1 genotypes. [20][21][22][23][24] Methodological rigor and quality were assessed using the STREGA recommendations. The total quality scores of the included studies ranged from 9 to 18 in the STREGA checklist.…”
Section: Data Extractionmentioning
confidence: 99%
See 3 more Smart Citations